Ecological Analysis of Health Resource Related to Measles at Primary Health Center in Indonesia (Medico Legal Update, 2021)
Measles is a vaccine-preventable disease. The case increases over the past 3 years in Indonesia. Thestudy aimed to analyze the correlation between health resources and measles. The ecological analysis wasconducted using secondary data from the Ministry of Health report in 2019. All provinces were taken assamples. Apart from measles cases as a dependent variable, while the independent variable consists of a ratioof public health center (PHC), a number of active Posyandu(Integrated Health Post), adequacy of midwives,availability of five typesof promotive-preventive health workers at PHC, availability of drug and essentialvaccine at PHC and the obedience of district drug warehouse to applied good management of drug andvaccine. The univariate analysis shows a descriptive table. Bivariate analyses were analyzed using a scatterplot. The results showa gap of measles cases between province in Indonesia were uneven. The highestmeasles cases occurred at Central Java (1.310cases) and the lowest at North Maluku (0 cases). The mean ofsuspect measles was 226, the higher cases of mean were dominated at Java. The variable of health workerand health logistic depict a random pattern with measles cases. It was concluded that the effectiveness ofhealth workers to prevent measles was measured by their performance. As well as optimizing the potentialof five types of promotive-preventive health workers at the PHC. The choice of method in distributionmanagement and vaccine management at the health center level must be a concern.